(untitled) (Praxis Educativa, 2023)
This article presents part of the results of a broader investigation in which the conceptions supported by the regulations developed by the Federal Council of Education (CFE) for teacher training in Argentina are analyzed. The article contains the main characteristics of the conceptual changes of the norms for teacher training related to teacher identity during the implementation of neoliberal policies of the 90s. It is a qualitative study that uses content analysis as one of the predominant methods for deepening the knowledge of social life.